A verification framework for stateful security protocols - LI, Li (Institutional Knowledge at Singapore Management University, 2017)
A long-standing research problem is how to efficiently verify security protocols with tamper-resistant global states, especially when the global states evolve unboundedly. We propose a protocol specification framework, which facilitates explicit modeling of states and state transformations. On the basis of that, we develop an algorithm for verifying security properties of protocols with unbounded state-evolving, by tracking state transformation and checking the validity of the state-evolving traces. We prove the correctness of the verification algorithm, implement both of the specification framework and the algorithm, and evaluate our implementation using a number of stateful security protocols. The experimental results show that our approach is both feasible and practically efficient. Particularly, we have found a security flaw on the digital envelope protocol, which cannot be detected with existing security protocol verifiers.